درجة توافر أبعاد القيادة التحويلية لدى مديري مدارس محافظة جنوب الباطنة بسلطنة عمان في ضوء نموذج ليثوود وآخرين "Leithwood et al. Model" - الحكمانية، سهام بنت خميس بن محمد; إبراهيم، حسام الدين السيد محمد (رابطة التربويين العرب, 2024)
هدفت الدراسة الحالية إلى عرف على درجة توافر أبعاد القيادة التحويلية لدى مديري مدارس محافظة جنوب الباطنة بسلطنة عمان في ضوء نموذج ليثوود وأخرين (Leithwood et al. Model)، واتبعت الدراسة المنهج الوصفي، كما استخدمت الاستبانة في جمع البيانات والمعلومات وتم تطبيقها على عينة مكونة من (١٧٤) معلما ومعلمة، وتوصلت نتائج الدراسة إلى أن درجة توافر أبعاد القيادة التحويلية لدى مديري مدارس محافظة جنوب الباطنة بسلطنة عمان في ضوء نموذج ليثوود وأخرين (Leithwood et al. Model) كانت عالية بصورة إجمالية، كما جاءت عالية في جميع أبعاد الدراسة وهي: بناء الرؤية المدرسية، وتحديد أهداف المدرسة، وإظهار توقعات عالية للأداء، وتوفير الدعم الفردي، وتقديم التحفيز الفكري، ونمذجة أفضل الممارسات والقيم التنظيمية المهمة، وإيجاد ثقافة مدرسية منتجة، وتطوير الهياكل التنظيمية لتعزيز المشاركة في القرارات المدرسية. كما كشفت النتائج عن عدم وجود فروق ذات دلالة إحصائية بين متوسطات تقديرات عينة الدراسة من المعلمين عند مستوى (α < 0.05) تعزى إلى متغيرات الجنس، وسنوات الخبرة، والمسمى الوظيفي، ولكن وجدت هذه الفروق في متغير المؤهل العلمي ولصالح حملة الماجستير. The present study aimed to identify The availability degree of transformational leadership dimensions among school principals in the South Al Batinah Governorate in the Sultanate of Oman in light of the Leithwood et al. Model, study used a descriptive method, also used the questionnaire to collect data and information were applied to a sample of (174) teachers. The results of the study reached that The availability degree of transformational leadership dimensions among school principals in the South Al Batinah Governorate in the Sultanate of Oman in light of the Leithwood et al. Model was came generally high degree ; It also came high in all dimensions of the study, which are: building the school vision, Establishing school goals, Demonstrating high performance expectations, Offering individualized support, providing intellectual stimulation, Modeling best practices and important organizational values, creating a productive school culture, and Developing structures to foster participation in school decisions. Results also showed that there were no significant differences at (α < 0.05) in the study variables which are sex, years of experience and job title, However, these differences were found in the academic qualification variable and in favor of master's degree holders.
Keywords: العملية التعليمية -- أبعاد القيادة التحويلية -- الثقافة التنظيمية -- الرضا الوظيفي